Salinity-Dependent Shift in the Localization of Three Peptide Transporters along the Intestine of the Mozambique Tilapia (Oreochromis mossambicus) - Con, Pazit; Nitzan, Tali; Cnaani, Avner (Frontiers in Physiology, 2017)
The peptide transporter (PepT) systems are well-known for their importance to protein absorption in all vertebrate species. These symporters use H+ gradient at the apical membrane of the intestinal epithelial cells to mediate the absorption of small peptides. In fish, the intestine is a multifunctional organ, involved in osmoregulation, acid-base regulation and nutrient absorption. Therefore, we expected environmental stimuli to affect peptide absorption. We examined the effect of three environmental factors; salinity, pH and feeding, on the expression, activity and localization of three PepT transporters (PepT1a, PepT1b, PepT2) along the intestine of the Mozambique tilapia (Oreochromis mossambicus). Quantitative real time PCR (qPCR) analysis demonstrated that the two PepT1 variants are typical to the proximal intestinal section while PepT2 is typical to the distal intestinal sections. Immunofluorescence analysis with custom-made antibodies supported the qPCR results, localized both transporters on the apical membrane of enterocytes and provided the first evidence for the participation of PepT2 in nutrient absorption. This first description of segment-specific expression and localization points to a complementary role of the different peptide transporters, corresponding to the changes in nutrient availability along the intestine. Both gene expression and absorption activity assays showed that an increase in water salinity shifted the localization of the PepT genes transcription and activity down along the intestinal tract. Additionally, an unexpected pH effect was found on the absorption of small peptides, with increased activity at higher pH levels. This work emphasizes the relationships between different functions of the fish intestine and how they are affected by environmental conditions.